Effectiveness of Digital Detox Interventions in Mitigating the Negative Effects of Social Media among Adolescents and Young Adults in Malawi - Mhone, Charity (International Journal of Psychology, 2023)
Purpose: The aim of the study was to investigate the effectiveness of digital detox interventions in mitigating the negative effects of social media among adolescents and young adults. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on digital detox interventions for Malawian youth is limited, but broader studies suggest effectiveness. These interventions reduce social media use, easing loneliness and anxiety while improving sleep. They also encourage offline activities, fostering social engagement and personal growth. Moreover, digital detox programs promote digital literacy, empowering critical social media navigation. Yet, sustaining benefits over time requires further investigation. Unique Contribution to Theory, Practice and Policy: self-determination theory (SDT), social cognitive theory (SCT) & cognitive-behavioral theory (CBT) may be used to anchor future studies on the effectiveness of digital detox interventions in mitigating the negative effects of social media among adolescents and young adults. By identifying effective components and delivery methods of digital detox interventions, practitioners can design interventions that are feasible, acceptable, and sustainable within various settings, including schools, communities, and healthcare facilities. Research on the effectiveness of digital detox interventions has implications for policy development aimed at promoting healthier digital environments.